1998
DOI: 10.1677/jme.0.0200157
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of both MCF-7 and Hs578T human breast cancer cell lines by vitamin D analogues is associated with increased expression of insulin-like growth factor binding protein-3

Abstract: The effects of two vitamin D analogues, EB1089 and CB1093, on insulin-like growth factor binding protein (IGFBP) expression have been examined in MCF-7 and Hs578T human breast cancer cell lines. Both vitamin D analogues inhibited IGF-1 stimulated growth of MCF-7 cells and enhanced the production of IGFBP-3 as determined by Western-ligand blotting. Recombinant human IGFBP-3 inhibited the growth of MCF-7 cells over the concentration range 1-235 ng/ml. Hs578T cells were unresponsive to the mitogenic effects of IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
2
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 0 publications
2
83
2
1
Order By: Relevance
“…Growth inhibition by IGFBP-3 has been reported in many cell lines such as Hs578T and MCF-7 breast cancer cells (Colston et al, 1998;Oh et al, 1993a). In the normal breast epithelial cell line, MCF-10A, it was recently reported that IGFBP-3 at 30 ng ml 71 also induced growth inhibition (Martin and Baxter, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth inhibition by IGFBP-3 has been reported in many cell lines such as Hs578T and MCF-7 breast cancer cells (Colston et al, 1998;Oh et al, 1993a). In the normal breast epithelial cell line, MCF-10A, it was recently reported that IGFBP-3 at 30 ng ml 71 also induced growth inhibition (Martin and Baxter, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b is a growth stimulator of fibroblast cells but is growth inhibitory in breast epithelial cells and mammary tumours (Daniel et al, 1996;Gold, 1999). Growth inhibitors such as TGF-b, retinoic acid and vitamin D (Colston et al, 1998) are potent regulators of IGFBP-3 and can stimulate IGFBP-3 at the mRNA level. TGF-b-induced growth inhibition seen in Hs578T breast cancer cells, as well as the TGF-b-induced proliferation seen in colon cancer cells and human airway smooth muscle cells is at least partially mediated by IGFBP-3 (Oh et al, 1995;Cohen et al, 2000;Kansra et al, 2000).…”
mentioning
confidence: 99%
“…It has been reported that both EB1089 and the anti-oestrogens tamoxifen and ICI 182 780 up-regulate IGFBP-3 and IGFBP-5 in MCF-7 cells, and suggested that both EB1089 and the anti-oestrogens mediate their growth inhibitory effect via up-regulation of IGFBP-3 and IGFBP-5 (Rozen et al, 1997;Colston et al, 1998), which are known to induce apoptosis in MCF-7 cells (Huynh et al, 1996a(Huynh et al, , 1996b. Our data showing the lack of cross-resistance between tamoxifen, ICI 182 780 and EB1089 reported in this study and in Lykkesfeldt et al (1995) indicate that different mechanisms are responsible for growth inhibition mediated by these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent evidence suggests that some IGFBPs may have direct receptor-mediated effects independent of IGFs (Oh et al 1993). IGFBP-3, for example, has been demonstrated to be an important mediator of other growth inhibitory agents, such as retinoic acid , vitamin D (Colston et al 1998), TGF- (Oh et al 1995, Rajah et al 1997, anti-estrogens (Huynh et al 1996), tumor necrosis factor- (Rozen et al 1998) and p53 (Buckbinder et al 1995), independently of the IGF signaling system. Furthermore, the importance of IGF-independent biological effects of the IGFBP superfamily, such as IGFBP-3 (Oh et al 1993), IGFBP-rP1 (Burger et al 1998) and -rP2 (Hishikawa et al 1999) on cell replication has been demonstrated in human breast cancer cell systems.…”
Section: Introductionmentioning
confidence: 99%